2009
DOI: 10.1016/j.jpainsymman.2008.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Survival with the Palliative Performance Scale in a Minority-Serving Hospice and Palliative Care Program

Abstract: Palliative Performance Scale (PPS) scores have shown potential for prognosticating survival in Caucasian samples, but have not been studied for prognostic value in cancer patients from minority groups. Using data obtained from a retrospective chart audit of 492 cancer patients admitted over an 18-month period to a minority-serving home-based hospice and palliative care program, we examined the relationship between PPS scores and length of survival (survival days). Patients with PPS scores of 10% to 30% had few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 14 publications
(42 reference statements)
0
63
0
2
Order By: Relevance
“…5 As a measure of functional status, we included the Palliative Performance Scale (PPS), which has been widely studied as a predictor of survival in hospice and palliative care populations. [5][6][7][8] The PPS is scored from 0 to 100 in 10-point increments to create an 11-point scale in which higher numbers correspond to better functional status. We also considered clinical variables that have not been studied as predictors of prognosis in this population, but which are plausibly associated with poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…5 As a measure of functional status, we included the Palliative Performance Scale (PPS), which has been widely studied as a predictor of survival in hospice and palliative care populations. [5][6][7][8] The PPS is scored from 0 to 100 in 10-point increments to create an 11-point scale in which higher numbers correspond to better functional status. We also considered clinical variables that have not been studied as predictors of prognosis in this population, but which are plausibly associated with poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…18 In a study by Weng et al, which assessed the relationship between PPS and days survived by patients with cancerous diseases, the survival rate found was lower: PPS≤30% -6 days, PPS=40% -19 days, 50%≥PPS -34 days. 19 In view of these results, it can be suggested that the PPS scale is used routinely as a predictive prognosis factor. The prognostic evaluation is important for the implementation of PC and, consequently, for adequate control of the symptoms of patients, with subsequent improvement of their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic evaluation is important for the implementation of PC and, consequently, for adequate control of the symptoms of patients, with subsequent improvement of their quality of life. [18][19][20] An important piece of data noted in this study was that patients with mild symptoms presented worsening of such in the second assessment conducted by the researcher. This fact allows us to deduce that these symptoms are poorly diagnosed and, thus, poorly controlled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such prognostic factors provide more accurate clinical information about patients to their physicians. Among them, Palliative Performance Scale (PPS) is one of most commonly used tool to evaluate patient' (10), numerous studies showed prognostic value of PPS (7,(11)(12)(13)(14)(15). PPS consisted of five parameters (ambulation, activity and evidence of disease, self-care, intake, and level of consciousness) which are mainly focused on patient's physical function.…”
Section: Introductionmentioning
confidence: 99%